Single radial hemolysis test for quantitation of complement-fixing antibodies to non-hemagglutinating viruses. - Fulton, R E (1984)
A single radial hemolysis test, which overcomes many of the problems of conventional complement fixation tests, was developed for the quantitation of virus complement-fixing antibodies. The test procedure utilized staphylococcal protein A-coated sheep erythrocytes immobilized in agarose into which antigen was incorporated. Undiluted heat-inactivated serum samples were allowed to diffuse radially from wells punched in the agarose. Protein A served to concentrate the subsequent antigen-antibody reaction on the surface of the erythrocytes. Zones of hemolysis were developed by flooding with complement. With adenovirus as a model, basic test parameters were defined, and optimum reagent concentrations and diffusion conditions were determined. A positive linear relationship was found to exist between zone diameter and increasing log concentration of specific antiserum. No correlation was found between zone diameter and total concentration of immunoglobulin G in test sera. Sera rendered anticomplementary by the addition of carrageenan produced hemolytic zones equal to diameter to those observed with untreated sera. Seventy-seven human sera with known complement fixation titers were tested by this method. Good correlation (r = 0.74) between the complement fixation test and single radial hemolysis was observed. This test was highly reproducible and more sensitive than the conventional complement fixation test.